Strategi Bauran Pemasaran Dan Dampaknya Terhadap Penjualan Pada Ud. Sari Bumi Di Kota Probolinggo ( Studi kasus pada Pelanggan UD. Sari Bumi Kota Probolinggo ) - Halimatus Sya’diyah; Nur Hidayati; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to analyze the effect of product, price, distribution and promotion on sales volume. The sample used in this study was 73 respondents who were UD consumers. Sari Bumi while the data collection technique used a questionnaire. The analytical method used is multiple linear regression analysis with the help of SPSS 16.0. The results of this study indicate that the product has a positive and significant effect on sales volume as well as prices, promotions and distribution to UD consumers. Sari Bumi Probolinggo. Keywords: Product, Price, Distribution, Promotion and Sales Volume